DEVELOPMENT MODEL FUTSAL (BEYB) APPROACH STRATEGY TRAINING - B, Benny (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The purpose of research and development have produced a model practice futsal attacking and defending approach training strategy in the game of futsal. In addition, research and development is carried out to obtain in-depth information about the development and implementation of training models and examine the effectiveness, efficiency models are made.Research and development research method development Research & Development (R & D) from Borg and Gall. Subjects in research and development are Se Futsal Player of Makassar.Test the effectiveness of the model using test instruments and test Attacking survive to collect data capabilities futsal players. Research data analysis using t test with significance level 0:05. Analysis of data obtained by the average value of this type of training to attack pre-test 23.47 and an average post test 35.27, standard deviation of the pre-test and post-test 1,049 1,087. While the average value of the model last pre test 14.67 and an average post test 22.22, standard deviation of 4.136 pre test and post test training models 2,998.Rata average strike pre-test and post test -11.80 and standard deviation 1.29 -71.07 t value, significance (2-tailed) 0.000 with a significance level of 0.05, H0 is rejected. While the average model of practice last pre-test and post-test -7.550 and a standard deviation of 2.931 -19.953 t value, significance (2-tailed) 0.000 with a significance level of 0.05, H0 is rejected. Based on the information it can be concluded that this type of training exercise last attack and the model approach in the game futsal training strategy developed can be applied effectively and efficiently so as to improve the skills playing futsal.